Descrição histológica do tecido ósseo do domo timpânico, estimativa de idade e crescimento em cativeiro do Peixe-boi da Amazônia Trichechus inunguis (Natterer, 1883) Mammalia, Sirenia - Albuquerque Júnior, Dagoberto Pinder (Instituto Nacional de Pesquisas da Amazônia - INPA, 2003)
The bone tissue is the most resistam structure of the Iwdy of vertebrates. Structurally, the bone tissue can be differentiated according to the arrangement and quantity of its extraceiiuiar matrix components in three distinct iayers: the primaiy, secondary and the third vascular iayers. The aim of this study was to describe histoiogicaiiy the differem constituem eiements of the bone tissue present in the tympanic dome of the Amazonian manatee emphasizing the aspect of the decaidfied extraceiiuiar matrix. its main ceiiuiar types, and their disposition within each of the three iayers. The tympanic domes of 70 Amazonian manatees deposHed in iNPA's Aquatic Mammais Coiiection were analyzed. The method described by Marmontei (1993) was used, which consists in demineraiizing a smaii 3mm section from the central portion of the tympanic dome in a commerciai demineraiization agent (RDO) to make cuts in a frozen microtome. thus obtaining veiy thin 40 pm thick sections. These micro sections were then stained using Harris' hematoxilin, and then mounted on slides using puie glycerin and seaied with Enteiian. Two hundred and eighty slides were made and lead under an optic microscope. The primaiy vascular iayer was characterized by the irregular disposition of coiiagen fibeis and numerous osteocyte lacunas loosely disposed. Havers systems and Voikmann channeis w/eie aiso observed randomiy inserted in the matrix bone. The secondary vascular iayer possessed coiiagen fibers endosed in lacunas, givmg a iameiiar appearance to the matrix bone. Aithough a simiiarity in the consHtution of the matrix bone between the primary and secondary iayers was fbund. the Havers systems and the Voikmann channeis of the secondary Iayer piesented a more organized appearance than the primary iayer. Finaiiy the third Iayers of the bone tissue was characterized by the presence cf Growth Layers Groups (GLGs) ali aiong the upper boider of the tympanic domes of animais oider than 1 year. A considerably small number of osteocyte lacunas were obsenred in comparison to tfie primary and secondary vascular iayers. and were aiways found side by side. Havers systems and Voikmann channeis were rareiy evident in this third Iayer. suggesting a compact bone appearance.
Keywords: Crescimento do Peixe-boi; Tecido ósseo - Histologia - Peixe-boi; Trichechus inunguis; Mammalia sirenia